Поселення ранньоскіфського часу Любомирка-1 у верхів’ї р. Тясмин - Орлик, О.П. (Археологія, 2007)
Опубліковано знахідки скіфського часу, виявлені біля с. Любомирка, що на Кіровоградщині, які засвідчують існування
тут поселення VI ст. до н. е. Поселение раннескифского времени у с. Любомирка-1 в верховье р. Тясмин по ведущим типам лепной посуды
можно датировать в пределах VI в. до н. э., хотя встречаются отдельные находки VIII —VII вв. до н. э., а ножка
протофасосской амфоры относится к концу VI — началу V вв. до н. э. Based on the main types of hand-made pottery the new settlement of Scythian times near the village of Lyubomyrka in the upper
part of Tyasmyn River region should be dated within the 6th c. BC, while some finds should be dated from the 8th—7th cc. BC,
and the stem of proto-Thasos amphora is dated from the end of 6th — the beginning of 5th cc. BC.